Regulation of kallikrein-related peptidases in the skin – from physiology to diseases to therapeutic options - Fischer, Jan; Meyer-Hoffert, Ulf (Thrombosis and Haemostasis, 2013)
Kallikrein-related peptidases (KLKs) constitute a family of 15 highly conserved serine proteases, which show a tissue-specific expression profile. This made them valuable tumour expression markers. It became evident that KLKs are involved in many physiological processes like semen liquefaction and skin desquamation. More recently, we have learnt that they are involved in many pathophysiological conditions and diseases making them promising target of therapeutic intervention. Therefore, regulation of KLKs raised the interest of numerous reports. Herein, we summarise the current knowledge on KLKs regulation with an emphasis on skin-relevant KLKs regulation processes. Regulation of KLKs takes place on the level of transcription, on protease activation and on protease inactivation. A variety of protease inhibitors has been described to interact with KLKs including the irreversible serine protease inhibitors (SERPINs) and the reversible serine protease inhibitors of Kazal-type (SPINKs). In an attempt to integrate current knowledge, we propose that KLK regulation has credentials as targets for therapeutic intervention.
Keywords: Atopic dermatitis; rosacea; Netherton syndrome; LEKTI; proteinase activated receptor; LL-37